Bullous cellulitis caused by Pseudomonas putida in a patient with end-stage renal disease - Salabei, Joshua K. (IDCases, 2020)
We present a case of bullous cellulitis in a 75-year-old male caused by Pseudomonas putida (P. putida) acquired from contact with contaminated water. Careful documentation of P. putida soft tissue infection is warranted given the rise in infections, marked antimicrobial resistance, and fatalities observed in a limited number of cases.